Planning Process for Kekasewa Village Development Kecmatan Ndona Ende Regency - Abraham Badu (Journal of Social Science, 2023)
This study intends to describe the development planning process at the grassroots level where the selected location is Kekasewa Village, Ndona District, Ende Regency, East Nusa Tenggara. Specifically, this research is aimed at describing the development planning process at the research location and identifying and explaining the supporting and inhibiting factors. Through qualitative descriptive research, it is described more accurately from observations made in full about a symptom or social situation including through observation and interviews. Some of the selected informants are government officials, community organizations and community members. The analysis was carried out by examining the data obtained from various sources and informants. The results obtained from this study indicate that (1) the application of participatory principles in the process of planning development programs in the village of Kekasewa can be said to be running even though it does not fully follow the principles of, by and for the community, (2) the process of planning development programs in the village Kekasewa has carried out a participatory development program planning process, the steps of which include: reviewing the situation or reviewing the situation, identifying future needs, identifying available resources and agreeing on a plan. In addition, the results that can be recorded from the field show that of the four main factors that influence the participatory planning process at the research location, two of these factors (the existence of mutual trust and democratic agreement) are proven to be supporting factors in the planning process of development programs/activities. As for the other two factors (professionalism of human resources and understanding of development issues themselves) in general they have not shown their role in supporting the "smooth" process of development program planning and have instead become obstacles to the planning process. Regarding the results of the research above, several important things that are recommended in this study are (1) maintaining the existing planning process because it essentially fulfills the principles of the community by the community and for the community. Even if there must be corrective steps, it is recommended to sharpen and reinforce the function and role of the Musbangdus and Musbangdes forums as a vehicle for screening/selection by applying a priority scale, (2) considering the function of the Musbangdus and Musbangdes as a means or medium of dissemination for existing proposed plans, whether those proposed by residents or sectoral plan proposals, (3) utilizing customary institutions through a joint agreement with the village government to instill relevant values ??to all members of the community to pay more attention to time issues, for example through "wora nau" (meaningful messages) conveyed by the mosalaki the day before the meeting, and (4) raising awareness through training regarding self-help surveys to identify potential or other forms of participatory rural appraisal (PRA).